Measuring the publishing productivity of economics departments in Europe - Chatzimichael, Konstantinos; Kalaitzidakis, Pantelis; Tzouvelekas, Vangelis (My University, 2017)
In this paper, we assess the relative performance of economics departments in Europe using publication data in a core set of thirty-five top research journals in economics during the period 2007-2011. We measure performance on the basis of a publishing productivity index which allows to account for differences in research inputs among departments. The measurement of publishing productivity index is based on counts of quality-adjusted articles per faculty using journal-weights computed over the same period with our study. Based on publishing productivity performance, comprehensive rankings are constructed at both department and country level.
Keywords: Economics departments; Universities rankings; Publishing productivity; Europe